Enhancing Analog Electronics Education in Undergraduate Degrees Through Digital Spine-Enabled Hybrid Passive-Active Learning Design - Ke Wang; James Scott; Margaret Jollands (IEEE Access)
The field of analog electronics remains core to modern technology, being critical to a wide range of applications, such as telecommunications, robotics and biomedical devices. However, its reliance on hands-on and iterative design processes presents unique challenges for traditional learning and teaching designs. In particular, traditional laboratory settings highly limit the weekly laboratory practice opportunities. In recent years, in the education research society the flipped classroom model, an active learning method, has emerged as a transformative pedagogical approach in higher education across various disciplines. In this paper, we discuss the design and application framework of a new hybrid passive-active learning approach in analog electronics, which partially leverages the flipped classroom model and partially utilizes the traditional passive model. Evaluation results show that this new hybrid passive-active learning approach has significantly improved learning outcomes, skill acquisition, and student engagement in analog electronics education in undergraduate degrees.